NUTRITIONAL STATUS AND SOME RELATED FACTORS OF TYPE 2 DIABETES PATIENTS MANAGED AT HA NAM GENERAL HOSPITAL IN 2021-2022 (Vietnam Journal of Community Medicine, 2022)
A cross-sectional study was conducted on 421 patients with type 2 diabetes from ≥ 20 years oldat Ha Nam Provincial General Hospital. Objective: Describe nutritional status and some relatedfactors. Method: Cross-sectional description. Results: According to the classification of the WorldHealth Organization Office for the Western Pacific (WPRO), the results showed that the percentageof study subjects with normal BMI was 46.8%; overweight and obesity was 53.2%. The prevalenceof overweight and obesity in men was 56.3% higher than that of women 49.7%. Some factors relatedto overweight and obesity have statistical significance (p < 0.05): The high waist/hip ratio group hasrisk of obesity 2.55 times higher (95% CI: 1.08 - 6) than that of the normal waist/hip group. Theeconomic well-off/rich group has higher risk of obesity 3.04 times (95%CI: 2.04 – 4.55) than thepoor/medium economic group.
Keywords: Diabetes, nutrition status, Ha Nam General Hospital.